ELECTRONIC REGISTRATION OF SECOND RANK MORTGAGE RIGHTS ON COLLATERAL OBJECTS WITH ADMINISTRATIVE VILLAGE CHANGES - Mariatun, Lisna; Muhjad, Hadin (JILPR Journal Indonesia Law and Policy Review, 2025)
The purpose of this research is to analyze the registration of Second-Ranking Electronic Mortgage (Hak Tanggungan) over collateral objects that have undergone an administrative change in their urban village (kelurahan) designation, with a case study in Selat Subdistrict, Kapuas Regency. The type of research used is normative legal research, which involves inventorying and analyzing statutory regulations. The nature of the research is prescriptive-analytical, aimed at finding legal solutions to existing issues from the perspective of the researcher.The first research finding reveals that the registration of a second-ranking electronic mortgage over a collateral object that has experienced a change in administrative location (from Selat Tengah to Selat Barat) cannot be carried out if the first-ranking mortgage has already been registered. This is because an administrative update to the collateral object’s location must first be conducted. In the Computerized Land Activities System (KKP), a collateral object already encumbered by a first-ranking mortgage is registered as an active mortgage record until that activity is concluded through a mortgage release (roya). Therefore, to update the location from Selat Tengah to Selat Barat, the existing mortgage record must be closed first. The second finding shows that, as an effort to maintain their position as the holder of the first-ranking mortgage, the creditor may based on the Mortgage Law (UUHT) ssue a Power of Attorney to Grant Mortgage (SKMHT) in accordance with Article 15 of the UUHT, followed by the release of the first-ranking mortgage based on Article 18 paragraph (1) letter b, which allows the mortgage to be released by the mortgage holder. Afterward, the administrative location update of the collateral object from Selat Tengah to Selat Barat can be processed. Once the data has been validated, the creditor can then execute a new Deed of Granting Mortgage (APHT) to re-register the first-ranking mortgage based on the SKMHT.